3D-Printed Hydrogels from Natural Polymers for Biomedical Applications: Conventional Fabrication Methods, Current Developments, Advantages, and Challenges - Berk Uysal; Ujith S. K. Madduma-Bandarage; Hasani G. Jayasinghe; Sundar Madihally (Gels)
Hydrogels are network polymers with high water-bearing capacity resembling the extracellular matrix. Recently, many studies have focused on synthesizing hydrogels from natural sources as they are biocompatible, biodegradable, and readily available. However, the structural complexities of biological tissues and organs limit the use of hydrogels fabricated with conventional methods. Since 3D printing can overcome this barrier, more interest has been drawn toward the 3D printing of hydrogels. This review discusses the structure of hydrogels and their potential biomedical applications with more emphasis on natural hydrogels. There is a discussion on various formulations of alginates, chitosan, gelatin, and hyaluronic acid. Furthermore, we discussed the 3D printing techniques available for hydrogels and their advantages and limitations.